Adsorption of β-carotene onto mesoporous carbon coated monolith - Muhammad (2011)
The mesoporous carbon coated monoliths (MCCM) were developed by dipcoating method using furfuryl alcohol (FA) as a carbon precursor and poly(ethylene glycol) (PEG) as a poreformer. The effect of molecular weight of PEG, carbonization temperature and PEG composition on the synthesis of MCCM were studied. The maximum specific surface area and mesopore area obtained were 61.13 m2/g and 49.39 m2/g. The pore size distribution of the carbon coated monolith exhibited two main peaks. One peak was located at 2.0 nm and the other at 3.6 nm. The pore size distribution curve indicated that the porous carbon was bimodally distributed. The MCCM was utilized as an adsorbent for adsorption of β-carotene from isopropyl alcohol (IPA) and n-hexane miscellas. The effect of temperature on the adsorption was investigated by batch adsorption experiments. The adsorption quantity increased with increasing temperature. The maximum adsorption capacity of β-carotene obtained was 62.118 mg/g for IPA at 50 °C. The experimental results were fitted using the Langmuir and Freundlich isotherms. The Langmuir described the adsorption process better. The negative values of Gibbs free energy change suggested that the adsorption was a spontaneous process. The positive values of heat of enthalpy and entropy change confirmed the endothermic nature of the adsorption. The adsorption kinetics of β-carotene onto mesoporous carbon coated monolith in isopropyl alcohol (IPA) and n-hexane solution was investigated, as functions of temperature and β-carotene initial concentration. Adsorption capacity increased as initial β-carotene concentration and temperature increased. In addition, the solvents also play an important role in the adsorption of β-carotene; adsorption kinetic of β-carotene by using IPA is higher than n-hexane. Two kinetic models, namely the pseudo-first-order and pseudo-second-order, were used to predict the adsorption kinetics. The rate parameters of the intraparticle diffusion model for adsorption were also evaluated to identify the adsorption mechanisms. The results clearly showed that the adsorption of carotene onto MCCM followed the pseudo-first-order model for IPA, and pseudo-second-order model for n-hexane solvent. The energy activation parameters were 11.45 and 9.41 kJ/mol for IPA and n-hexane, respectively. Sorption kinetics of β-carotene in IPA solution was analyzed at different temperatures and initial concentrations by using the linear driving force (LDF) model. The software MATLAB® was used to solve the LDF model simultaneously with the adsorption equilibrium isotherm at liquid/solid interface. The linear driving force mass transfer coefficient (kLDF) obtained was increased with increasing temperature. However, the LDF model did not describe experimental results satisfactorily at high initial concentrations. The equilibrium and kinetics of desorption process of β-carotene from MCCM were investigated in a batch system. The MCCM was first saturated with β-carotene from IPA solution. The β-carotene was then desorbed by using n-hexane solution. The data of desorption were evaluated by two models i.e. linear isotherm and Freundlich isotherm. The desorption was satisfactorily fitted with the Freundlich model. The desorption kinetic was analyzed using a first-order two-compartment three-parameter model. The activation energy obtained was 7.88 and 44.47 kJ/mol for rapid and slow desorption, respectively.